Relación entre seguridad alimentaria y entornos alimentarios en colonias vulnerables del área conurbada de la Ciudad de México - Totosaus, Alfonso (Horizonte Sanitario, 2024)
Objective: In this research, the relationship between food security level and socioeconomic status, food environment perception, and shopping habits was determined. Materials and Methods: A descriptive analysis to determine the relationship between food security status and socioeconomic characteristics, and food environment perception was conducted. Data was collected by surveys in vulnerable neighborhoods of Ecatepec de Morelos, México. Results: Food insecurity was predominantly a consequence of the socioeconomic conditions, although the places to buy foods seem to be adequate since there is no preference for where to buy, by distance or price, finding fresh fruits and vegetables, representing a healthy, cheap, and affordable diet. Nonetheless, the barriers to buying foods were price and income, limiting the quality and amount of food to buy, denoting the necessity to expand open-air markets operation, to bring affordable and healthy food in poor neighborhoods within conurbation capital cities areas. Conclusion: Enhancing affordable foods is necessary to improve food insecurity status for families living in poor neighborhoods. Keywords: Food security, Social vulnerability, Poverty, Environment and public health.